2021
DOI: 10.1088/2053-1591/abdf1b
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-based alloy surfacing process optimization and surfacing material performance analysis

Abstract: In order to solve the problem of the failure of the UMCo50 process burner, the orthogonal test was used to optimize the UMCo50 cobalt-based alloy TIG surfacing process, better joint performance was obtained for welding current of 120 A, surfacing speed of 12 cm min−1, interpass temperature of 50 °C and surfacing layer of 2 ∼ 3 layers; Tungsten inert gas(TIG) welding and plasma transferred arc weld(PTAW) surfacing were used to surfacing UMCo50 welding wire and T800 cobalt-based alloy powder on UMCo50 base metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…in order to save cost and improve efficiency, it is generally necessary to repair the outer end face of the failed burner and put it into use again. Xue et al [11] reported that t800 cobalt-based alloy powder is surfacing on the uMCo50 substrate. it is found that there are more Laves phases in the surfacing layer, which is beneficial to improve the hardness and wear resistance of the surfacing layer.…”
Section: Introductionmentioning
confidence: 99%
“…in order to save cost and improve efficiency, it is generally necessary to repair the outer end face of the failed burner and put it into use again. Xue et al [11] reported that t800 cobalt-based alloy powder is surfacing on the uMCo50 substrate. it is found that there are more Laves phases in the surfacing layer, which is beneficial to improve the hardness and wear resistance of the surfacing layer.…”
Section: Introductionmentioning
confidence: 99%